Bidirectional causal link between inflammatory bowel disease and celiac disease: A two-sample mendelian randomization analysis - A, Gu; Sun, Caixia; Shan, Yuezhan; Husile, Husile; Bai, Haihua (Frontiers in Genetics, 2022)
Abstract Background: Observational research has shown a correlation between inflammatory bowel disease (IBD) (comprising ulcerative colitis (UC) and Crohn’s disease (CD)) and celiac disease. However, the relationship between these two diseases remains uncertain. Methods: We utilized two-sample Mendelian randomization (MR) to estimate the bidirectional causal relationships between IBD and celiac disease. This study utilized data on single nucleotide polymorphisms (SNPs) from genome-wide association studies (GWASs). Heterogeneity, pleiotropy, and sensitivity analyses were also performed to evaluate the MR results. Results: There was a significant causal relationship between IBD and CD and celiac disease (e.g., IBD and celiac disease, inverse variance weighting (IVW) odds ratio (OR) = 1.0828, 95% CI = 1.0258-1.1428, p = 0.0039; CD and celiac disease, IVW OR = 1.0807, 95% CI = 1.0227-1.1420, p = 0.0058). However, in the reverse direction, we found only suggestive positive causality between celiac disease and CD (e.g., IVW OR = 1.0366, 95% CI = 1.0031-1.0711, p = 0.0319). No evidence of heterogeneity between genetic variants was found (e.g., IBD vs. celiac disease, MR-Egger Q = 47.4391, p = 0.6159). Horizontal pleiotropy hardly influenced causality (e.g., IBD vs. celiac disease, MR-Egger test: p = 0.4340). Leave-one-out analysis showed that individual SNPs did not influence the general results. Conclusion: Our MR analysis revealed a positive causal link between IBD and celiac disease in the European population. In addition, several recommendations for disease prevention and clinical management have been discussed.